Evaluating the accuracy and reliability of compound‐specific carbon isotopic analysis using gas chromatography‐combustion‐isotope ratio mass spectrometry with the addition of a reduction furnace. (23rd December 2022) - Cao, Yunning; Liu, Hu; Hu, Jing; Wang, Zheng; Zhu, Mengshu; Liu, Xu; Yang, Kaili; Gan, Haijiao; Liu, Weiguo
Abstract : Rationale: Gas chromatography‐combustion‐isotope ratio mass spectrometry (GC/C/IRMS) is widely used for compound‐specific carbon isotopic analysis. However, current isotopic analysis systems utilize the GC IsoLink combustion reactor, and independent reduction furnaces are not implemented. Therefore, whether this limitation in furnace use affects the precision of compound‐specific carbon isotopic analysis needs to be evaluated. Methods: We attempted to add a separate reduction furnace to the GC IsoLink interface and compared the δ 13 C values of n ‐alkanes (including C and H elements), fatty acid methyl ester (including C, H, and O elements), caffeine (USGS61 and USGS62, including C, H, O, and N elements), and 9‐ethylcarbazole (including C, H, and N elements) before and after the addition of the reduction furnace using the GC IsoLink combustion reactor. Results: For n ‐alkanes and fatty acid methyl esters, the δ 13 C differences between the measured values and their standard values were basically falling within 0.5‰ whether or not an independent reduction furnace was added. However, for the nitrogen‐containing compounds (caffeine and 9‐ethylcarbazole), the δ 13 C differences between the measured values and their standard values were much larger without an independent reduction furnace (1.0–3.71‰ for USGS61, 1.78–2.19‰ for USGS62, and 0.39–1.13‰ for 9‐ethylcarbazole) than with a reduction furnace (−0.31–0.68‰ for USGS61, −0.44–0.06‰ for USGS62, and −0.04–0.25‰ for 9‐ethylcarbazole). Conclusions: The addition of an independent reduction furnace had no significant effect on the δ 13 C of n ‐alkanes and fatty acid methyl esters, but it had a significant effect on the δ 13 C of nitrogen‐containing compounds. It is suggested that GC IsoLink needs an independent reduction furnace to effectively eliminate the interference of NOx on CO2 isotopic determination to improve the accuracy of δ 13 C for nitrogen‐containing compounds.